HIGH-RESOLUTION GEOMORPHOLOGICAL MAPPING OF THE SHALLOW CONTINENTAL SHELF WEST OF THE KAVALA BAY, NORTH AEGEAN - Panagiotopoulos, I.P.; Kapsimalis, V.; Ioakim, Chr.; Karageorgis, A.; Rousakis, G.; Morfis, I.; Hatiris, G.A.; Anagnostou, C.; Koukoulis, A.; Papatrechas, Ch.; Koutsovitis, P.D.; Economou, G.; et al. (Bulletin of the Geological Society of Greece, 2016)
Prominent geomorphological features of the shallow continental shelf west of the Kavala Bay (Loutra Eleftheron-Nea Peramos) were mapped using the data from a hydrographic survey (June 2014) of 320 nautical miles during which high resolution multibeam bathymetry and seismic-reflection subbottom profiling were carried out simultaneously. A fault zone comprised by a set of two primary sigmoidal gravity faults (recorded lengths and measured offsets: 12 km, 5 km and > 40 m, 25 m, respectively), with distinct expression on the seabed, and three other secondary gravity faults situated southern of the major faults, revealing synsedimentary tectonics, was identified. The striking difference between the texture of the footwall block sediments of the northern major fault and the texture of the sediments occupying the deep hanging wall block of the southern major fault emphasizes the impact of local tectonics on the sedimentary evolution of the study area. Concerning the observed bedforms, the most interesting were the sand dunes occurring at depths from 25 m to 65 m at least and occupying the northeast part of the study area. Their large dimensions and orientation in relation to the coastline position imply as a mechanism for their formation intense bottom-current activity.